A influência do YouTube e TikTok na visão empreendedora dos estudantes de administração de uma instituição de ensino superior - Sousa, Rayra Viana de (Brasil, 2024)
The promotion of online entrepreneurship is due to the convergence of two forces: technological progress and the democratization of access to information, especially driven by social networks. The main objective of this research is to examine the influence of YouTube and TikTok videos on the entrepreneurial vision of business students at a Higher Education Institution. The methodology consists of descriptive research of a qualitative and quantitative nature, as statistical and content analyses were performed based on the data collected. Data collection was carried out through a questionnaire answered by 73 students of the administration course at the chosen institution. The main results indicate that the lack of incentives for entrepreneurial culture within the educational institution encourages students to seek information and content about entrepreneurship on social networks such as YouTube and TikTok. Furthermore, the influence of these social networks on students' entrepreneurial vision is notable, as these platforms offer democratic access to information, tutorials and inspiring stories, which can spark interest and motivation to undertake. This research contributes scientifically to the understanding of the role of digital technologies in the training of entrepreneurial professionals.